Triangle of Tension: How Social System, Market Forces & Journalistic Autonomy Influence Web Analytics Use. (3rd July 2022) - Dollah, Siti Rahil Binte; Tandoc Jr., Edson C.
ABSTRACT: This study seeks to understand how newsrooms negotiate and navigate their way in adopting and using web analytics within an environment where the influence of the social system interacts with the influences of market forces and journalistic autonomy. Based on interviews with 22 editors and journalists from 13 publications in Singapore, this study finds two interesting trends: First, news organisations in Singapore follow closely how web analytics is used in newsrooms in the West and have embraced it but are cautious and selective, especially when it touches on sensitive issues like politics, race, and religion. Second, conceptualisations of web analytics use in earlier research conducted in the Western context is less significant in Singapore where its use accentuates a triangle of tension between three forces: the social system, journalistic autonomy, and market values. The findings show a need to expand the understanding of the place of web analytics in journalism—and how individual journalists adopt and adapt it in their news work—beyond the dominant market-forces-versus-journalistic-autonomy framework, especially in contexts where social system structures exert strong influences on journalism.